Takhrij and Syarah Hadith of Agrotechnology: Farming and Planting Agriculture - Meutia Rizki; Wahyudin Darmalaksana; Yayan Mulyana; Ahmad Taofik (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith with respect to agriculture. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is the excessive use of inorganic fertilizers or pesticides. The conclusion of this research is the takhrij and sharah of the Prophet’s traditions regarding the excessive use of inorganic fertilizers and their impact on pests so it would be better if you use organic fertilizers.